THE INFLUENCE OF JOB SATISFACTION AND LEADERSHIP STYLE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDY AT PT IDE JAYA KREASINDO) - Pratikto, Bagus Tri; R Sudiarditha, I Ketut; Sholikhah, Sholikhah (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
The purpose of this study is : 1) To know the description of job satisfaction and the leadership style on Organizational Citizenship Behavior (Study at PT Ide Jaya Kreasindo) 2) To know the effect of job satisfaction on Organizational Citizenship Behavior 3) To know the effect of the leadership style on Organizational Citizenship Behavior 4) To know the effect of job satisfaction and the leadership style on Organizational Citizenship Behavior simultaneously. Research methods using simple random sampling. Sampling technique using simple random sampling technique and of questionnaires of 77 observations from PT Ide Jaya Kreasindo’s employees using SPSS 16.0.The empirical result shows that job satisfaction and the leadership style has positive and significant effect on organizational citizenship behavior. Simultaneously test shows that job satisfaction and the leadership style effects organizational citizenship behavior. Keywords: Job Satisfaction, The Leadership Style, Organizational Citizenship Behavior